The Effect of Using Content-Purpose-Audience (CPA) Strategy toward Students’ Writing of Analytical Exposition Text at the Eleventh Grade of SMA Nurul Falah Pekanbaru - Dahler Dahler (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2017)
The research was conducted at eleventh grade SMA Nurul Falah Pekanbaru inteaching writing analytical expoition text. The researcher used Content-Purpose-Audience (CPA) strategy because the strategy could facilitate the language skillsparticularly writing. The purpose of this research were to find out significant toeffect of using Content-Purpose-Audience (CPA) strategy toward students’writing ability in analytical exposition text at the eleventh grade students of SMANurul Falah Pekanbaru. The type of this research was quasi-experiment research.The numbers of participants in this research were 62 eleventh grade students ofSMA Nurul Falah Pekanbaru. The sample of this research by using clusterrandom sampling. The sample of this research were classes XI.IIS.2 as theexperimental class and XI.IIS.1 as control class. Instrument used in this researchwas test. In collecting the data, researcher gave the test write analytical expositiontext. The data was analyzed by using SPSS. The researcher found that the valueSig. (2-tailed) from the control class and experimental class is 0.001 < 0.05, it isreject Ho. It means there was different ability between students’ score of theexperimental class and control class in terms of writing an analytical expositiontext. Thus, it can be concluded that the strategy Content-Purpose-Audience (CPA)effective for teaching writing analytical exposition text.